A successful initial management of a penetrating head trauma in a rural district hospital: Case report - S. Kohpe Kapseu; C.H. Esseme Ndjie; V. Tchokonte-Nana (Trauma Case Reports)
Penetrating head trauma is the most fatal form of head injury. Although many cases of penetrating head trauma have been reported in the literature, its management remains complex, requiring a multidisciplinary team, which makes it a challenge in district hospitals where human resources and technical equipment are limited.We aim to present a successful initial management of a case of penetrating head trauma in a rural district hospital before a transfer to a first category hospital. A 27-year-old man, smoker with no pathology history was involved in a road accident, falling from a motorbike without a helmet. In admission to our rural district hospital, the Glasgow Coma Scale during physical examination was 6/15 with bilateral mydriasis, haemodynamic distress and good saturation. A penetrating head injury was identified with profuse intracranial haemorrhage. Intracranial packing known in damage control neurosurgery to tamponade severe intracranial haemorrhage and which is a lifesaving neurosurgical manoeuvre was used. The patient was transferred unconscious to a first-category hospital, free of intubation and in a stable haemodynamic state. The post-operative period was marked by convulsive seizures, for which the patient was put on anticonvulsants with a good outcome. At rural district hospital level, when faced with a penetrating head trauma, the principles of neurosurgical damage control must be well-known in order to optimise the use of available resources.